Porous and geometry-resolved CFD modelling of a lattice transmission tower validated by drag force and flow field measurements. (1st August 2018) - Allegrini, Jonas; Maesschalck, Jan; Alessi, Giacomo; Glabeke, Gertjan; Christophe, Julien; van Beeck, Jeroen
Highlights: Design codes cannot accurately predict drag forces for complex transmission towers. Drag forces of a scaled complex transmission tower are measured in a wind tunnel. Flow fields in the wake of different sections of the tower are measured with PIV. The flow fields show that most parts of a transmission tower act as a porous media. A computationally efficient porous media CFD model is used to predict drag force. Abstract: The assessment of the aerodynamic forces acting on transmission towers is of crucial importance for their design. These predictions are mainly based on an extrapolation of wind tunnel measurements done on simple structures which are the base of the present design codes. This extrapolation results in an uncertainty which often leads to insufficiently accurate drag force predictions, because of a lack of agreement between the basis of the design codes and their use for tall and complex tower geometries. Therefore, in the present study drag forces are measured in a wind tunnel on a scaled transmission tower and three representative sections of it. Results show similar drag coefficients for the entire tower and the different sections it is composed of. Additionally, the flow fields in the wake of these structures are measured with PIV (Particle Image Velocimetry). With low lattice densities the effect of each lattice element can be seen in the wake, while the lattice structures act as a porous media for higher densities. Based on these results a CFD (Computational Fluid Dynamics) approach, in which the transmission tower is modelled as a porous media, is proposed in this paper. The CFD simulations are performed substituting the tower geometry with a representative porous model, decreasing considerably the computational time and cost of the simulations. A validation against the experiments and classical CFD simulations, where the detailed geometries are resolved, is performed and shows the applicability of the developed approach. The drag forces as well as the velocity deficit in the wake of the transmission tower are well predicted with the porous CFD simulations. For regions with low lattice densities the porous CFD simulations cannot predict the effect of individual lattice elements on the flow field, because the individual lattice elements are not explicitly resolved.